Is Self-Expression Chic? Globalisation, Value Change and Convergence in Latin America - De Oliveira De Castro, Henrique Carlos; Capistrano, Daniel; Ranincheski, Sonia; Bisong Tambe, Elvis (Revista Latinoamericana de Opinión Pública, 2020)
The literature concerning human values change, argues the main factor driving increasing levels of secularization and self-expression is the improvement of material conditions. In fact, studies succeeded to present evidence of the strong relationship between GDP and post-materialist attitudes at the national level. Still, in this study, we demonstrate this relationship is not as strong in Latin America. Based on the theory of mass-elite convergence of values, we argue that the main factor driving value change in Latin America is globalisation and not economic development. With globalisation, attitudes and values hitherto exclusive to the elites became socially desirable and praised (chic) resulting in their massive dissemination. Using data from the World Values Survey, we confirm that variables related to material conditions are the best predictor for secularization and self-expression among Western European countries. However, in Latin America, the effects of economic development are weaker, and the evidence indicates that variables related to social globalisation are more important to explain value change patterns.